Overcoming reading comprehension deficits: the efficacy of the SQ3R method across barrett’s cognitive levels - Kemil Wachidah; Sella Lailatul Qumayroh (Jurnal Bidang Pendidikan Dasar, 2026)
Reading comprehension is an important skill that needs to be developed in elementary school because it supports students’ academic success and literacy development. However, many students still experience difficulties in understanding reading texts. This study aimed to examine the effectiveness of the SQ3R (Survey, Question, Read, Recite, Review) method in improving the reading comprehension skills of fourth-grade students at UPT SDN 175 Gresik. This research used a quantitative approach with a pre-experimental one-group pretest–posttest design. The participants were fourth-grade students selected using a saturated sampling technique. Data were collected through reading comprehension tests before and after the implementation of the SQ3R method and analyzed using normality tests and paired sample t-tests. The results showed that the SQ3R method had a positive and significant effect on students’ reading comprehension skills. Therefore, the SQ3R method can be used as an effective strategy to improve reading comprehension in elementary school students.